Inclusive inquiry: a compassionate journey in trauma-informed qualitative research with GBV survivors from displaced communities - Diab, Jasmin Lilian; Al-Azzeh, Dana (Frontiers in Psychology, 2024)
The integration of trauma-informed and ethical frameworks in qualitative research concerning survivors of gender-based violence (GBV) within displaced communities is critical. These individuals often bear the weight of traumatic experiences compounded by displacement and associated hardships. Adopting a trauma-informed approach establishes a safe environment, prioritizing survivors’ well-being and respecting their agency and narratives, thereby fostering trust and reducing re-traumatization risks. Ethical considerations ensure the dignity, rights, and cultural sensitivities of participants are upheld, contributing to rigorous and humane research. This integration amplifies survivors’ voices and experiences, enhancing understanding and empathy. Trauma-informed approaches acknowledge the likelihood of trauma in individuals’ lives and prioritize safety without aiming to treat symptoms. Proficient interviewing skills aim to improve comfort, safety, and recall without avoiding challenging questions. Integration of trauma-informed principles across all interview phases is crucial, particularly for individuals experiencing various traumas simultaneously, such as displacement, violence, and ongoing conflict. Drawing from the authors’ experiences and existing literature, this paper advocates for a compassionate and empowering shift in qualitative research methodologies to better engage with survivors of trauma and GBV within displaced communities.